2018
DOI: 10.3390/molecules23082049
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Estimation of the Cytotoxicity and Genotoxicity of Root Extract from Leonurus sibiricus L. Overexpressing AtPAP1 against Different Cancer Cell Lines

Abstract: As the current cancer treatment success rate is not sufficient, interest has grown in plants as possible sources of anti-cancer compounds. One such plant with a broad spectrum of activity is Lenourus sibiricus of the family Lamiaceae. This study investigates for the first time both the genotoxic and cytotoxic activities of TR (transformed) and AtPAP1 TR (with over-expression of transcriptional factor) root extracts of Lenourus sibiricus against various cancer cell lines (CCRF-CEM, K-562 and A549). Both tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Many studies have shown that plant extracts or pure compounds isolated from plants are able to induce apoptosis in various types of cancer [22,[30][31][32]. Although revolutions in the modern drug industry have given rise to a trend of replacing herbal remedies with modern drugs, studies of natural compounds from herbal plants and their activities are still of interest for drug discovery; they are not only characterized by better absorption but also by lower toxicity than chemical drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that plant extracts or pure compounds isolated from plants are able to induce apoptosis in various types of cancer [22,[30][31][32]. Although revolutions in the modern drug industry have given rise to a trend of replacing herbal remedies with modern drugs, studies of natural compounds from herbal plants and their activities are still of interest for drug discovery; they are not only characterized by better absorption but also by lower toxicity than chemical drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to measurements, the cells were centrifuged (300× g for 10 min at 22 • C) then washed twice with the HBSS. Further procedure has been described previously [22,23].…”
Section: Mitochondrial Membrane Potential (Mmp)mentioning
confidence: 99%
“…The cell growing process was performed in a humidified incubator at 37 • C and 5% CO 2 . To perform the analysis cells were seeded at 3 × 10 6 cells per well and were left in the incubator for 12 h before treatment procedures [34]. Next, the cell samples were incubated with melittin in a concentration range of 0.001 to 100 µM for 24 h and 48 h. As a positive control (S)-(+)-camptothecin was used in three different concentration-10, 50 and 100 µM.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Prior to measurements, the cells were centrifuged (300× g for 10 min at 22 • C) then washed twice with the HBSS. Finally, the fluorescence was measured on a Bio-Tek Synergy HT Microplate Reader according to our previous study [24].…”
Section: Mitochondrial Membrane Potential (∆ψM)mentioning
confidence: 99%